Analysis of Implementation the Medical Records System in Puskesmas UPT Medan Tuntungan - Yudica Rosalina; Peberiwati, Peberiwati; Iskandar Chandra (Jurnal Info Sains : Informatika dan Sains, 2023)
A medical records are one of the most important units in a health center. Medical records contain notes and documents regarding patient identity, examinations, treatment, procedures and other services provided to patients. One component of health services to determine the quality of health services is the availability of medical record data. The aim of this research is to find out the description/implementation of medical records in the medical records unit at the UPT Puskesmas Medan Tuntungan and to find out the system for implementing medical records starting from patient registration to file storage, with a descriptive research method with a qualitative approach with a sampling method using the snowball sampling technique. and with a qualitative research design